Evaluation of Islamic Education in Tuna Grahita Students at The Extraordinary High School C (SMALB-C) Putera Asih Kediri - Alfin Husniyah; Ahsana Taqwiyan; Dariyanto Dariyanto; Dariyanto (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
The government has committed to be providing educational services for its citizens who are born with various abnormalities through the provision of special education as a realization of UU No. 20 Tahun 2003 pasal 5 ayat (2). The writing of this article aims to explore further the reality of Islamic Religious Education (Pendidikan Agama Islam/PAI) implementation in special education institutions at the senior secondary level located at SMALB-C Putera Asih Kota Kediri. The approach used in this research is qualitative approach with case studies as the type of research. Meanwhile, the data in this study were collected through interviews, observation, and documentation.As for data analysis techniques, we adopt the Miles, Huberman, & Saldana model which includes data condensation, data display, and conclusions drawing. From the results of the research, it can be concluded that: 1) The planting of PAI in the classroom which is carried out through learning activities for mentally retarded students at SMALB-C Putera Asih Kota Kediri in general can be said to be good, considering that the implementation is in accordance with the prepared lesson plan. Meanwhile, the implementation of PAI outside the classroom, one of them is carried out through Dhuha prayers in congregation every day. 2) Evaluation of PAI for mentally retarded students at SMALB-C Putera Asih Kota Kediri can be said to have not run optimally, since the assessment still relies on the cognitive aspects only. Meanwhile, for the affective and psychomotor aspects, both have not been implemented properly.